Mathematical simulation of fluid flow and analysis of flow pattern in the flow path of low-head Kaplan turbine - A. V. Rusanov; O. N. Khoryev; S. A. Riabova; D. Y. Kosianov; P. N. Sukhorebryi; N. M. Kurskaya (Журнал інженерних наук)
The results of numerical investigation of spatial flow of viscous incompressible fluid in flow part of Kaplan turbine PL20 Kremenchug HPP at optimum setting angle of runner blade φb = 15° and at maximum setting angle φb = 35° are shown. The flow simulation has been carried out on basis of numerical integration of the Reynolds equations with an additional term containing artificial compressibility. The differential two-parameter model of Menter (SST) has been applied to take into account turbulent effects. Numerical integration of the equations is carried out using an implicit quasi-monotone Godunov type scheme of second - order accuracy in space and time. The calculations have been conducted with the help of the software system IPMFlow. The analysis of fluid flow in the flow part elements is shown and the values of hydraulic losses and local cavitation coefficient have been obtained. Comparison of calculated and experimental results has been carried out.